USE OF ASSESSMENT TECHNIQUES AND HUMAN RESOURCES MANAGEMENT IN SCHOOL ADMINISTRATION - ODUNAYO, ODUNAYO HENRY ADEWALE (Sokoto Educational Review, 2025)
This study investigated assessment techniques and human resource management in school administration. Proper assessment helps inform effective human resource management strategies for school administration. Two hypotheses guided the research. A descriptive survey research design was used to study a large sample of participants, allowing for generalization of the findings. A simple random sampling technique selected 120 participants, including school principals and teachers from 15 senior secondary schools in Ojo LGA, Lagos State. Data were collected using a 20-item close-ended self-designed questionnaire on Assessment Techniques and Human Resources Management in School Administration (QATHRMSA). The instrument was validated for both content and construct validity. A split-half reliability index of 0.873 indicated good internal consistency. Data analysis was performed using Pearson Product-Moment Correlation, and hypotheses were tested at a 0.05 significance level. The study found that both appropriate assessment techniques and human resource management have a significant relationship with effective school administration. It concluded that human resource management is a key component in identifying human-related factors that drive effective school administration.